Legal Protection for Suspects through the Integration of Judicial Supervision in Pre-Trial Detention in Indonesia - Erwin Susilo; Dharma Setiawan Negara; Joel Niyobuhungiro (IJCLS (Indonesian Journal of Criminal Law Studies), 2025)
Pre-trial detention is a serious action that deprives individuals of their freedom and must be carried out by the principle of legality to protect human rights (HAM). In the Indonesian criminal justice system, detention is regulated by the Criminal Procedure Code, which requires two pieces of evidence and meets subjective and objective requirements. However, the pretrial mechanism used to test the legality of detention is still administrative and limited to requests. However, Indonesia's current pretrial detention mechanism remains predominantly administrative and dependent on detainee initiation, failing to fully comply with Article 9(3) of the ICCPR. Specifically, Indonesia does not consistently ensure immediate physical presentation of detainees before a judicial officer (commonly within 48 hours), lacks automatic judicial review of detention legality without requiring detainee action, and does not provide sufficient judicial scrutiny to assess the necessity and proportionality of continued detention, as exemplified by practices in Germany (§114 StPO) and the Netherlands (Article 57 Sv). This condition creates the potential for abuse of authority and human rights violations. This research uses normative legal research methods that examine legal principles, statutory regulations, doctrine, and legal theory related to pre-trial detention in the criminal justice system. This research identifies systemic weaknesses in Indonesia’s pretrial detention through comparative analysis. It introduces three innovative elements to the conception of integrated judicial supervision: Tiered Judicial Review Mechanism, Burden-Shifting Protocol, and Digital Monitoring Integration. The proposed ideal conception involves integral judicial oversight, in which judges have a direct role from the start of detention to ensure its legality. This system integrates supervision of the legality of detention in the criminal justice process, provides more optimal protection for suspects, and meets international human rights standards. This step is expected to create a more efficient, accountable justice system that aligns with the principles of the rule of law.